Cogging force issues of permanent magnet linear generator for electric vehicle - Abdalla, I.I. (Engineering and Scientific Research Groups, 2017)
Alternatives to hydraulic drives that used on vehicles are necessary in order to reduce the Carbon dioxide (CO2) emission and oil consumption. Hence better performance and efficiency of the vehicles can be achieved by using free piston engine, in which the piston reciprocate linearly with a permanent magnet linear generator (PMLG) without the need of a crankshaft. The PMLG has high performance, but suffering from the cogging force. The cogging force induces undesired vibration and acoustic noise and makes a ripple in the thrust force. Moreover, the cogging force deteriorates the control characteristics, particularly in terms of the position control and speed precisely. This paper proposes Somaloy to replace the laminated silicon steel sheets in order to reduce the cogging force in a PMLG. Through a finite-element analysis, it has been shown that, the stator core made of Somaloy minimizes the cogging force of the PMLG, moreover, giving larger flux-linkage and back-electromotive force (B-EMF), respectively. © JES 2017.